Croton Production and Use - Robert H. Stamps; Lance S. Osborne (EDIS, 2003)
Crotons have been popular in tropical gardens for centuries. Crotons grow into shrubs and small trees in their native habitats of India, Malaysia, and some of the South Pacific islands. Few other plants can surpass them in both foliage color and leaf shape variation. Since some cultivars are tolerant of interior environments, crotons have also become very popular as interior potted foliage plants. One additional point, often overlooked, is that foliage of crotons is excellent material for use in floral arrangements. Both individual leaves and entire branches can be used in floral designs. This document is Circular ENH878, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date March 2003.